A NON-THESIS PROGRAM FOR MASTERS' CANDIDATES. - Lorig, Arthur N. (The Accounting Review, 1958)
Abstract The article discusses some changes introduced in the masters of business administration degree (MBA) course at the University of Washington at Seattle in Washington D.C. Some of these changes include that the MBA degree aspirant will be given a choice of a thesis or non-thesis program. The Master of Arts student, who is more likely to aim toward teaching and hence toward the doctorate will, still require writing a thesis. The non-thesis program requires the student to take three special research courses of three quarter-credits each. This total of nine credits corresponds to the nine allowed for an accepted thesis under the thesis program. The classes customarily will meet one day a week for two or more hours. The first count will be taken in the first or second quarter of enrollment as an MBA student. In it the student will be taught research methodology, including statistical, survey, analytical, market research, and operations research methods. During this quarter the student in the non-thesis program will select a topic on which he will write a major paper during the next two quarters. He will begin his research at this time. A student under the thesis program also may enroll in and receive credit for this course, but not the other two courses in the series.